PENGARUH SPIRITUALITAS, INTELEKTUALITAS, DAN PROFESIONALISME TERHADAP KINERJA DOSEN STAIN SALATIGA - Abdul Aziz Nugraha Pratama (State Institute of Islamic Studies (IAIN) Salatiga, 2014)
This study aims to determine the effect of each variable spirituality, intellect, and professionalism of the lecturers performance STAIN Salatiga. The population of this study are all tenured State Institute of Islamic Studies (STAIN) Salatiga as many as 107 people. The sampling technique used in this study using simple random sampling and 65 were taken as respondents. With quantitative methods and analysis techniques that use moderated regression analysis (MRA), it can be concluded that (1) spirituality is partially not significantly affect the performance of the faculty; (2) the partial intellect does not significantly affect the performance of the faculty; (3) professionalism partially positive and significant effect on the performance of the lecturer. (4) spirituality, intellect and professionalism of lecturers jointly affect the performance of the lecturer. The study also found that the majority of respondents aged very productive, but they are staying at very far away from the campus.